Segmentative function of prosody in discourse - Don, Zuraidah Mohd. (Journal of Modern Languages, 2017)
The central focus of this article is to present a description of the prosodic features manifested in Malay spoken discourse and the segmentative function they perform in their loci of occurrences. To attain this goal, the study relies on a detailed analysis of transcribed recordings of selected fragments of Malay broadcast interviews. By adopting a descriptive framework that recognises prosody as consisting of prosodic resources such as pitch, loudness, tempo and pause, I am able to present a formal characterisation of prosodic realisations in Malay spoken discourse. And by examining these prosodic cues in a segmentational system in the context of adjacency pairs, I am able to account for the relationship between prosodic manifestations and the segmentative function they fulfill in actual interaction. The article presents argument for segmenting discourse into units of speech whose boundaries are defined by audible phonetic cues. The conclusion is that this less restrictive framework enables the identification of the prosodic cues involved in segmentative work and the roles that the segmented chunks play in discourse development.